Perfect : a novel - Joyce, Rachel (Random House, 2013)
Byron Hemmings wakes to a morning that looks like any other: his school uniform draped over his wooden desk chair, his sister arguing over the breakfast cereal, the click of his mother's heels as she crosses the kitchen. But when the three of them leave home, driving into a dense summer fog, the morning takes an unmistakable turn. In one terrible moment, something happens, something completely unexpected and at odds with life as Byron understands it. While his mother seems not to have noticed, eleven-year-old Byron understands that from now on nothing can be the same.